Posterior Transdural Approach for Odontoidectomy in a Child: Case Report. (1st September 2019) - Archer, Jacob B; Thatikunta, Meena; Jea, Andrew H
Abstract: INTRODUCTION: The transoral transpharyngeal approach is the standard approach to resect the odontoid process and decompress the cervicomedullary spinal cord. There are some significant risks associated with this approach, however, including infection, CSF leak, prolonged intubation or tracheostomy, need for nasogastric tube feeding, extended hospitalization, and possible effects of phonation. Recently, a posterior transdural approach was used to resect retro-odontoid cysts in 3 adult patients. We sought to use a similar approach to perform a posterior transdural odontoidectomy METHODS: We present the case of a 12-yr-old girl with Down syndrome and significant spinal cord compression from basilar invagination and a retro-flexed odontoid process. We performed a posterior transdural odontoidectomy prior to occiptocervical fusion. RESULTS: At 12-mo follow-up, we report satisfactory clinical and radiographic outcomes with this approach. CONCLUSION: In carefully selected patients, a posterior odonoidectomy is a viable approach that can safely provide adequate ventral decompression of the spinal cord.